Peran Pegadaian Syariah dalam Literasi Keuangan Syariah - Tulasmi Tulasmi; Titania Mukti (Jurnal Ilmiah Ekonomi Islam, 2020)
This study aims to determine the implementation of the Indonesian National Financial Literacy Strategy (SNLKI) in the sharia pawnshop sector in Yogyakarta. The data collection technique in this study is a structured interview method that is asking q5uestions that have been prepared to the respondent, which is then recorded by the researcher. The answers to the interview questions are then called primary research data. The population of this study is all branches of sharia pawning in Yogyakarta and researchers took samples with Probability Sampling because each element of the population is homogeneous, which has the same opportunity to be chosen as the subject. The results of this study are that all sharia pawnshop unit offices have implemented programs to improve financial literacy but have not been optimal in understanding specifically the SNLKI issued by the government due to the lack of training from the center regarding the core action of SNLKI.